(untitled) (Dimensión Empresarial, 2022)
The objective of this study was to determine the relationship among Organizational Climate, Boreout, and Innovation in companies in the agroindustrial sector in Montería, Colombia. This research is quantitative, non-experimental, of a correlational cross-sectional cohort, which uses an analysis of variance for data analysis. The results showed that the Organizational Climate influences the Bore out Syndrome and this, in turn, on innovation, which will allow a better understanding of the factors, which affect innovation processes in this economic sector and contribute to the development of future strategies, which improve innovation management. Finally, the obtained results will allow organizations and their managers to take actions, which allow boosting innovation processes through manipulation of factors, which affect their innovative performance, by improving eventually their competitiveness.